An observational study to evaluate the outcome of patients admitted in pediatric intensive care unit (PICU) using pediatric risk of mortality (PRISM-III) score in a tertiary care hospital of West Bengal - Sudipto Paul; Kanai Lal Barik; Nilanjan Ghosh; Sumanta Laha; Sayan Bera; Sukanya Nath (Asian Journal of Medical Sciences, 2023)
Background: Pediatric risk of mortality (PRISM III) score is used across the globe to predict the mortality of hospitalized children by an objective method based on 17 variables measured during first 24 h of admission in pediatric intensive care unit (PICU).